The treasure hunt : a story about geography and maps - Alexander, Liza.; Prebenna, David ([Racine, Wis.] : Western Pub. Co. in conjunction with Children$1 (Bs Television Workshop,s, 1990)
Elmo and Big Bird use a map to look for treasure.
"A Golden book"--Cover.
"A Sesame Street/Golden Press book."